Awareness and Attitude Regarding the Health Risks and the Consumption of Ultra-Processed Foods - Muhammad Atif Dawach; Syed Muhammad Hameez Qadri; Shoaib Khan (`, 2025)
The global nutritional landscape has shifted significantly in recent decades, moving from traditional whole food diets to those dominated by processed and ultra-processed foods (UPFs). The prevalence of UPFs has led to their widespread incorporation into global food systems, raising public health concerns. This study aims to examine the relationship between awareness, attitudes, and consumption of UPFs. A sample size of 369 was determined, rounded to 400 for accuracy. Data were collected from Gulshan-e-Johar and Gulshan-e-Iqbal in Karachi, Pakistan’s largest city. The statistical analysis was performed by the help of Statistical Package for Social Science (SPSS-27). The Chi-square test findings indicating a significant link between knowledge and intake of ultra-processed foods (UPFs) (χ² = 218.738, df = 4, p <.001). This shows that changes in UPF intake are closely connected to awareness levels, rather than independent of them. Those participants have much awareness they consume less amount of ultra-processed foods. It is also observed that those participants keep positive attitude they consumed a good amount of ultra-processed foods. Mostly label reader’s high consumption of ultra-processed foods were noted. Keywords: Ultra-Processed Foods Consumption, Awareness, Attitude, Health Risk